Computer-aided design of novel HIV-1 entry inhibitors blocking the virus envelope gp120 V3 loop - Andrianov, A.M.; Anishchenko, I.V.; Kisel, M.A.; Kornoushenko, Yu.V.; Nikolayevich, V.A.; Eremin, V.F.; Kucherov, I.I.; Tuzikov, A.V. (Вiopolymers and Cell, 2012)
Aim. The object of this study was to implement computer-aided design of the water-soluble analog of glycolipid β -galactosylceramide (β-GalCer), which presents a potential HIV-1 entry inhibitor, by the analysis of intermolecular interactions of β-GalCer with the central region of the virus envelope gp120 V3 loop followed by synthesis of this glycolipid derivative and testing for antiviral activity. Methods. To reach the object of view, computer modeling procedures, such as quantum chemical calculations, molecular docking, molecular dynamics and free energy simulations, were involved in the studies in conjunction with chemical synthesis and anti-HIV-1 assay methods. Results. As a result, the high probability of exhibiting of antiviral activity was predicted for the designed β-GalCer analog. The data of molecular modeling were confirmed by those of primary medical trials of the synthesized compound. Conclusions. In the light of the findings obtained, the designed analog of β-GalCer may be considered as the basic structure for simulation of its more potent structural forms and for posterior selection of drug candidates most promising for synthesis and anti-HIV-1 assays. Keywords: HIV-1 gp120 V3 loop, glycolipids, computer modeling, chemical synthesis, anti-AIDS drugs.